DIGITAL BRANDING SEBAGAI OPTIMALISASI PENINGKATAN INOVASI, DAYA SAING, PENDAPATAN UKM DI ERA NEW NORMAL - Ardana, Rizki Amalia HM; Rafidah, Rafidah; Erliyana, Nova (Universitas Sahid, 2023)
The increasingly rapid development of business certainly creates very tight competition, and the UKM sector is no exception. In addition, the presence of digital technology presents online businesses that provide opportunities and threats for UKM. In an increasingly fierce competition, UKM are required to continue to innovate, be creative and innovative in their business so that they are not immersed in market competition and this needs to be done to increase the income of UKM themselves. This study aims to find out how digital branding is implemented as an optimization of increasing innovation, competitiveness, and UKM income in the city of Jambi in the new normal era, a case study of UKM actors in the Kota Baru sub-district of Jambi. In this study using a qualitative approach that is descriptive, data collection methods by observing, interviewing and documentation. The data collection technique in this study used a purposive sampling technique. The informants in this study were UKM in Kota Baru District, Jambi. The results of this study indicate that the implementation of digital branding has been optimized by several UKM, but there are still UKM who have not optimized the implementation of digital branding in their business. Lack of knowledge about digital use, old age, capital, and lack of follow-up from the local government regarding the application of digital branding to UKM.